The Contribution of Agricultural Sector on Economic Growth of Nigeria - Sertoglu, Kamil; Ugural, Sevin; Bekun, Festus Victor (International Journal of Economics and Financial Issues, 2017)
Agriculture is a panacea for economic growth (Gunner Myrdal, 1984). The battle for long-run economic growth is either won or lost in the agricultural sector. However, how this path births economic prosperity has been the subject of debates among economist and development scholars. This study empirically examines the impact of agricultural sector on the economic growth of Nigeria, using time series data from 1981 to 2013. Findings revealed that Real Gross Domestic Product (RGDP), agricultural output and oil rents have a long-run equilibrium relationship. Vector Error Correction Model (VECM) result shows that, the speed of adjustment of the variables towards their long run equilibrium path was low, though agricultural output had a positive impact on economic growth. It was recommended that, the government and policy makers should embark on diversification and enhance more allocation in terms of budgeting to the agricultural sector. Keywords: Agriculture, economic growth, time series, cointegration and vector error correction model (VECM). JEL Classifications: O13, Q32, Q33